2021
DOI: 10.1111/epi.16964
|View full text |Cite
|
Sign up to set email alerts
|

Cortical low‐frequency power correlates with behavioral impairment in animal model of focal limbic seizures

Abstract: Objective Impairment in consciousness is a debilitating symptom during and after seizures; however, its mechanism remains unclear. Limbic seizures have been shown to spread to arousal circuitry to result in a "network inhibition" phenomenon. However, prior animal model studies did not relate physiological network changes to behavioral responses during or following seizures. Methods Focal onset limbic seizures were induced while rats were performing an operant conditioned behavioral task requiring response to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…13 Focal hippocampal seizures in rats and mice induced by brief 2s, 60 Hz hippocampal stimulation also exhibit behavioral arrest and cortical slow waves resembling human temporal lobe seizures. [13][14][15][16][17][18] These findings established the validity of the rodent models for investigating impaired behavior and physiology in focal limbic seizures.…”
Section: Network Inhibition Hypothesis and Other Mechanismsmentioning
confidence: 89%
See 2 more Smart Citations
“…13 Focal hippocampal seizures in rats and mice induced by brief 2s, 60 Hz hippocampal stimulation also exhibit behavioral arrest and cortical slow waves resembling human temporal lobe seizures. [13][14][15][16][17][18] These findings established the validity of the rodent models for investigating impaired behavior and physiology in focal limbic seizures.…”
Section: Network Inhibition Hypothesis and Other Mechanismsmentioning
confidence: 89%
“…Rodent model studies have verified that cortical physiology during focal limbic seizures closely resembles states of decreased arousal such as deep anesthesia or sleep. Like in human limbic seizures, the cortex in rodent models shows slow waves, decreased CBF, and hypometabolism [13][14][15][16][17][18][19] (Figure 2). Cortical neuronal recordings showed Up and Down states of action potential firing and membrane potential oscillations mimicking the physiology of deep sleep and anesthesia.…”
Section: Network Inhibition Hypothesis and Other Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using rodent models have confirmed that the cortical physiology experienced throughout focal limbic seizures is nearly similar to low-arousal states such as deep anesthesia or sleep [5]. The brain of the mouse model exhibits steady waves, hypometabolism, and decreased cerebral blood flow, identical to human limbic seizures [6][7][8][9][10][11]. Membrane potential oscillations and action potential firing patterns in cortical neurons were recorded in up and down states, simulating anesthesia and deep sleep physiology [5][6][7][8]11,12].…”
Section: Introductionmentioning
confidence: 91%